2023
DOI: 10.1088/1361-6560/accd42
|View full text |Cite
|
Sign up to set email alerts
|

Fast D M,M calculation in LDR brachytherapy using deep learning methods

Abstract: \textbf{Objective:} The Monte Carlo (MC) method provides a complete solution to the tissue heterogeneity effects in low-energy low-dose rate (LDR) brachytherapy. However, long computation times limit the clinical implementation of MC-based treatment planning solutions. This work aims to apply deep learning (DL) methods, specifically a model trained with MC simulations, to predict accurate dose to medium in medium (D\textsubscript{M,M}) distributions in LDR prostate brachytherapy.\\

\textbf{App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The toolkit provides a brachytherapy package with several source geometries and a track-length estimator (TLE) for dose scoring (Williamson 1987). The simulation setup was done following Berumen et al (2023). Patient simulations were performed with the 125 I selectSeed model geometry.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toolkit provides a brachytherapy package with several source geometries and a track-length estimator (TLE) for dose scoring (Williamson 1987). The simulation setup was done following Berumen et al (2023). Patient simulations were performed with the 125 I selectSeed model geometry.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…As recommended by the TG-372 report, the local and global dose differences (equation ( 5)) are used to evaluate the output between advanced dose calculation algorithms in brachytherapy (Beaulieu et al 2023). For LDR prostate brachytherapy patients, Berumen et al reported that 90.1% of voxels had global dose differences in the [−1%, 1%] interval when comparing a single-seed dose predictor (based on a 3D UNet model) and the MC reference (Berumen et al 2023). These results are comparable to those presented in this work for the streamline UNet model.…”
Section: Dvh Metrics and Dose Difference Ratiosmentioning
confidence: 99%